The efficacy and safety of everolimus for the treatment of progressive gastroenteropancreatic neuroendocrine tumors: A multi‐institution observational study in Taiwan. Issue 4 (30th June 2016) - Liu, Chien‐Ting; Chen, Ming‐Huang; Chen, Jen‐Shi; Chen, Li‐Tzong; Shan, Yan‐Shen; Lu, Chang‐Hsien; Su, Yu‐Li; Ku, Fan‐Chen; Chou, Wen‐Chi; Chen, Yen‐Yang
Abstract: Aim: Everolimus is an inhibitor of mTOR, approved for treatment of advanced pancreatic neuroendocrine tumors (NETs). The purpose of this observational study was to evaluate the efficacy and safety of everolimus in treatment of progressive, advanced gastroenteropancreatic neuroendocrine tumors (GEP‐NETs) in Taiwan. Methods: Fifty‐three patients with progressive, advanced GEP‐NETs who received everolimus treatment between January 2008 and August 2014 were selected. Patient characteristics, tumor features, safety profiles and treatment efficacy were retrospectively analyzed. Results: Mean follow‐up duration was 23.7 (1.2–70) months and 37 of 53 patients (69.8%) remained alive at the end of study. The one‐ and two‐year overall survival rates were 90.5% and 75.4%, respectively. The median progression‐free survival (PFS) was 18.9 (95% confidence interval; 10.9–26.8) months. Partial response was observed in 15 (28.3%) patients, 29 (54.7%) patients had stable disease and nine (17%) patients had progressive disease. Patients with World Health Organization (WHO) grade I NETs, nonfunctional tumors and liver metastasis burden <10% had significantly better PFS with everolimus treatment. Adverse events observed were stomatitis (35.8%), hyperglycemia (22.6%) and rash (18.8%). Seven (15.4%) patients experienced severe adverse events (grade 3 or more), including hyperglycemia (4.4%), anemia (4.4%), fatigue (2.2%) and elevated liver function (2.2%). One (2.2%) patient died from grade 5 interstitial pneumonitis. Conclusion: Everolimus was an effective treatment for Taiwanese patients with progressive advanced GEP‐NETs. Patients with nonfunctional NETs had a trend toward longer PFS, whereas patients with liver metastases burden <10% had a trend toward longer overall survival time receiving everolimus treatment.